The future of EU-CIS trade - Erokhin, Vasilii (Henry Stewart Talks, 2014)
Overview of EU-CIS trade, Specifics of EU-Russia trade relations, EU trade policies, Trade integration within the CIS, Customs Union of Russia, Belarus and Kazakhstan